Prognosis following acute coronary syndromes according to prior coronary artery bypass grafting: Meta-analysis. Issue 6 (1st December 2015) - Teixeira, Rogério; Vieira, Maria J; Ribeiro, Miguel A; Gonçalves, Lino; Gersh, Bernard J
Abstract: Purpose: Conduct a meta-analysis to study the prognostic influence of a previous coronary artery bypass grafting (CABG) in patients admitted for an acute coronary syndrome (ACS). Methods: A systematic review of the literature was performed using electronic reference databases through January 2013 (MEDLINE, Cochrane Library, Web of Knowledge, Google Scholar and references cited in other studies). Studies in which ACS outcomes with a previous history of CABG were compared with ACS outcomes with no history of previous CABG were considered for inclusion. The main endpoints of interest were mortality and non-fatal acute myocardial infarction. Data was aggregated at three follow-up times using random-effects meta-analysis models. Results: Twenty-four studies were included which provided 387, 181 patients for analysis. Previous CABG ACS patients were older, more diabetic and had a more frequent history of a previous myocardial infarction. Pooled in-hospital mortality was higher for the previous CABG ACS patients (OR 1.22 [1.04–1.44], p <0.01, I 2 88%). The pooled adjusted OR showed no significant differences for the two groups (adjusted OR 1.13 [0.93–1.37], p =0.22, I 2 92%). Previous CABG ACS patient had a higher pooled 30-day mortality (OR 1.28 [1.05–1.55], p =0.02, I 2 74%); a higher non-adjusted (OR 1.61 [1.38–1.88], p <0.01, I 2 70%) and adjusted (adjusted OR 1.37 [1.15–1.65], p <0.01, I 2 0%) long-term mortality. Both the in-hospital and the long-term re-infarction rates were higher for the previous CABG ACS patients. Conclusions: According to our data, ACS patients with previous CABG history had a higher risk for short- and long-term adverse events.